Paroxysmal Orthostatic Ventricular Tachycardia in a Patient With Supine Hypertension and Orthostatic Hypotension - Khalil Kanjwal MD, FHRS; Shakeel M. Jamal MD; David W. McComb DO; Majid Mughal MD; Asim Kichloo MD (SAGE Publishing, 2020)
Supine orthostatic hypertension with orthostatic hypotension is an autonomic dysfunction where the patients present with hypertension when supine and with decrease in blood pressure while bearing an upright posture. We report on a 74-year-old male who was admitted with dizziness and was found to have profound orthostatic hypotension with supine hypertension. The patient also developed orthostatic paroxysmal premature ventricular beats as well as nonsustained ventricular tachycardia. In this report, we attempt to present the possible mechanism of orthostatic ventricular tachycardia in our patient and the overview of the treatment strategies used in management of patients with supine hypertension and orthostatic hypotension.